FOSTERING RELIGIOUS CHARACTER IN GENERATION ALPHA THROUGH RELIGIOUS ACTIVITIES AT PURBASARI KARANG JAMBU PURBALINGGA PUBLIC ELEMENTARY SCHOOL NO. 2 - Vivi Alvina Damayanti; Zen Magata Larashati (Jurnal Konseling Pendidikan Islam, 2026)
This research is motivated by the rapid technological developments in the digital era, which pose significant challenges in the formation of the religious character of the Alpha generation, especially at the elementary school level. This research is a field research conducted at SD Negeri 2 Purbasari, Purbalingga, using a qualitative approach through observation, interviews, and documentation studies. The focus of the research is the formation of students' religious character through religious activities, driving factors, and obstacles encountered. The results show that routine religious activities, such as Religious Friday, tadarus, congregational prayer, dhikr, and the use of interactive media, are effective in fostering religious values ​​in the dimensions of belief, practice, intellect, experience, and consequences. The process of forming religious character is carried out through teacher role models, habituation, and reinforcement, which is in line with modern character education theory and Al-Ghazali's concept of morality. Factors driving success include student enthusiasm, teacher and principal support, and parental involvement, while obstacles include technological distractions, limited facilities, and inconsistent habits at home. This research confirms that varied, enjoyable, and habit-based religious activities are an effective strategy for instilling religious character in the Alpha generation in the digital era.